Dinâmica organizativa do acesso dos usuários do PSF aos serviços e às práticas de saúde de média e alta complexidade - Araújo, Mariana de Oliveira (2014)
The access to health services in a global, equal and comprehensive way constitutes itself a civil right legally granted in the Brazilian Federal Constitution of 1988 which regulates and establishes the Unified Health System (SUS). However it is noticeable that the comprehensive access to health services has not been effectively put into practice, especially, in actions of medium and high complexity. Hence, this study aims to understand the organizational dynamic of the access of users of the Family Health Program (PSF) to the healthcare services of medium and high complexity of the SUS network and to analyze health practices performed by the primary care team, medium and high complexity for the feasibility of this access. We have analyzed the organizational dynamic of access to medium and high complexity healthcare services based on the guidelines of the dimensions of a political, technical and symbolical access analysis bounded by Giovanella and Fleury (1995) and supplemented with the theoretical model proposed by Assis et alii (2011). In the theoretical framework we discuss ways for the effectuation of the access to the healthcare services as a citizenship right as well as the organization of healthcare services in medium and high complexity under the focus of healthcare assistance models. This is a qualitative study, of critical and analytical approach in an approximate view of the dialectic method, which has as field of work the Family Health Units (USF), the Polyclinics and the Public Hospitals of Feira de Santana city in the State of Bahia. The participants of the study consisted of three groups: (1) healthcare professionals, (2) users and (3) managers/coordinators of healthcare services totaling 26 participants. We have used techniques such as data collection through semi-structured interviews, systematic observation and document analysis. The data analysis was an approximation of the hermeneutic-dialectic method. From the comparison of the studied data three categories rose up: (1) ORGANIZATIONAL DYNAMIC OF THE ACCESS OF THE USERS AND THE MATERIALITY OF ITS SENSES AND MEANINGS: the transversality of the political, technical and symbolical dimensions; (2) THE WORK PROCESS OF THE HEALTH PROFESSIONALS IN BASIC HEALTHCARE OF MEDIUM AND HIGH COMPLEXITY: an interweaving among healthcare; (3) THE ACCESS OF THE USERS TO THE SERVICES AND THE PRACTICES OF HEALTH OF MEDIUM AND HIGH COMPLEXITY: public/private relationship. The results make the senses/meanings of access to healthcare services that cross the political, technical and symbolical dimensions abundantly clear. The individual and collective practices, held by professionals working in primary care of medium and high complexity to promoting the access of the user to the SUS network, involve committed and welcoming actions by instituting bonds and enhancing the subjectivity of the users in some moments, and in other moments it involves a centered professional model geared towards the patients‟ concerns/conduct, medicalization and technicism co-existing dialectically an intertwining of lightweight, soft-hard and hard technologies in this process. Within the difficulties and limitations that the users have found to access healthcare services of medium and high complexity the demand was cited once these services are offered on a wider scale than its supply. We have come across several inputs used by users to access the health services of medium and high complexity. Furthermore the relationship between public and private is constitutive of the organization of this reality. The access of the user of the PSF to the practices of medium and high complexity still needs, for its embodiment, an all-embracing commitment of users, health professionals and health managers so as to operationalize it as a citizenship right.